Impact of silicon fertilization on crop growth, productivity and nutrients enhancement in rice: A review - Joy, M S; Neetu, S; Rakesh, K; Lalrammawii, C; Nihal, D; Hritik, S; Faraaz, F; Swati, M (Plant Science Today, 2025)
Silicon (Si), constituting around 27.7 % of the Earth's crust by weight, is the second most abundant element after oxygen (47 %). While not considered essential, silicon is beneficial for crop growth, especially for Poaceae family crops. Intensive cultivation or continuous mono-cropping of cereals like rice depletes soil silicon levels, which may lead to decreased rice yields. Rice can absorb and accumulate silicon metabolically, a trait not common in many upland crops. Beyond boosting rice yields, silicon offers multiple benefits, such as enhancing nutrient availability (N, P, K, Ca, Mg, S, Zn), reducing nutrient toxicity (Fe, Mn, P, Al) and mitigating biotic and abiotic stress in rice. Sufficient silicon also stabilizes rice plant culms, reducing lodging risks. Thus, silicon is crucial for plant growth and improving rice productivity at the agronomic level. This review focuses on the relationship between silicon and rice crops, their interactions with other elements and strategies for managing silicon in soils and plants to sustain rice productivity.